The Iranian nuclear program and the non-proliferation regime: dilemmas for the future - Gontijo, Raquel; Januario, Luiza Elena [UNESP] (Inst Brasileiro Relacoes Int, 2020)
The Iranian nuclear program has been a source of apprehension and concern for some time. There are suspicions that Iran aims to use nuclear energy for military purposes, becoming an illegitimate nuclear power. Decades of sanctions and attempts of negotiation have not had satisfactory results. This paper aims to analyze the actual framework of the Iranian nuclear issue and argues that it reflects the controversies and difficulties of the nuclear nonproliferation regime.
Keywords: Iran; United States; nuclear issue; Non-proliferation